Critical Discourse Analysis on Celebrity Case in Online News Headlines - Nadya Inda Syartanti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
This study aims to reveal the construction of the news about the immoral video case that happened to Indonesia’s celebrity (GA) in various online news media through Norman Fairclough's critical discourse analysis approach. Data sources are taken from various online news media, namely detik.com, kompas.com, liputan6.com, and tribunnews.com in the range of publications from November 2020 to January 2021 with the research subject in the form of news headlines related to GA’s immoral video case. With three dimensions of discourse from Norman Fairclough's critical discourse analysis, the data analysis was carried out by the three stages: the descriptive analysis stage, the interpretation analysis stage, and the explanation analysis stage. The results found that through the microstructural dimension, the eight news headlines used language tools by 1) choosing vocabulary that was focused on the various phrase of video X, and 2) grammatical units which were dominated by clauses, 3) syntactic functions which were dominated by information as topicalization of discourse, and 4) a form of news that emphasizes the affirmation or clarification of GA’s immoral video case. Then, through the mesostructure dimension, the four online mass media have different characteristics and characters in their delivery of news, especially news about the GA’s immoral video case, but are still presented accurately and objectively so that the news content can be conveyed to readers. Finally, through the macrostructural dimension, with the reporting of immoral video cases, GA received a negative image in the eyes of the Indonesian people, because she was considered to be contrary to eastern culture. This negative image is formed because of the news using vulgar, tendentious, and transparent language to reflect press freedom that must be upheld, even though in composing news, sometimes using sarcastic language and making comparisons in it to attract readers' interest